2014
DOI: 10.1016/j.exppara.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of free-living amoebae in streams of the Mexico Basin

Abstract: Free-living amoebae (FLA) are protozoa that are widely distributed in nature. They are important in the cycling of nutrients in aquatic food chains, but their distribution in natural aquatic environments is not well known. We conducted a survey to determine the presence and distribution of FLA and their relation to some physicochemical parameters in streams of the Mexico Basin in Central Mexico. Thirty-two sites from 18 streams were sampled. Samples were centrifuged and cultured onto NNA-media to isolate amoeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
1
20
0
2
Order By: Relevance
“…This is in agreement with previous studies that indicate that T2 Acanthamoeba genotype is mainly found in the environment and is phylogenetically related to T6 and they have also been both isolated from clinical AK cases in humans [40]. Acanthamoeba genotype T11 is closely related to T4 and has been found to also cause AK [33]. Acanthamoeba of T4 genotype is reported as the most commonly encountered T-genotype group in both environmental water and clinical samples and also the most diverse [33].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with previous studies that indicate that T2 Acanthamoeba genotype is mainly found in the environment and is phylogenetically related to T6 and they have also been both isolated from clinical AK cases in humans [40]. Acanthamoeba genotype T11 is closely related to T4 and has been found to also cause AK [33]. Acanthamoeba of T4 genotype is reported as the most commonly encountered T-genotype group in both environmental water and clinical samples and also the most diverse [33].…”
Section: Discussionsupporting
confidence: 92%
“…that were higher in the dry season. Most waterborne parasites increase in number during the rainy season due to contamination of the water sources with sewage, soil, and other organic matters from water run-off [5,33]. Tap water had a higher prevalence of FLA than the natural water source.…”
Section: Discussionmentioning
confidence: 99%
“…The page key is based on morphological character of free living amoebae such as trophozoites shape, pseudopodia shape and amoebae nucleus, endo and ecto-cysts in the cystic form. These criteria could lead to identification of amoeba at the family and genus level [11]- [13]. This study indicated the considerable contamination of recreational water sources in Tehran, Iran with free living amoebae.…”
Section: Methodsmentioning
confidence: 77%
“…En México, existe una falta de reportes sobre detección de estos organismos (Lares-Villa & Hernández-Peña, 2010;Bonilla-Lemus et al, 2014). Este abordaje en el estado de Tamaulipas es el primero de su clase y el primero en describir presencia de amibas de vida libres consideradas patogénicas.…”
Section: Discussionunclassified